Equilibrium optimizer tuned novel FOPID‐DN controller for automatic voltage regulator system. (6th May 2021) - Paliwal, Nikhil; Srivastava, Laxmi; Pandit, Manjaree
Summary: This paper presents a novel fractional‐order PID plus derivative with filter coefficient (FOPID‐DN) controller for automatic voltage regulator (AVR) system using the MATLAB/Simulink environment. An AVR system is employed in the power system to maintain the terminal voltage at the desired level. Parameters of the proposed FOPID‐DN controller are optimally tuned by the recently developed Equilibrium Optimizer (EO) algorithm. Performance of the designed FOPID‐DN controller for an AVR system is compared with various controllers which are optimally tuned by different optimization algorithms. Comparative transient response analysis of the proposed technique has been carried out by considering vital transient response indicators like maximum overshoot, rise time, and settling time. Performance analysis of the proposed technique for an AVR system has been done by considering several input conditions. Robustness analysis of the EO algorithm tuned FOPID‐DN controller has been performed by varying the time constants of different components in an AVR system. The capability of the FOPID‐DN controller to handle nonlinearities of an AVR system has been investigated. The stability of the FOPID‐DN controlled AVR system has been analyzed. In addition, the disturbance rejection capability of the FOPID‐DN controlled AVR system has also been investigated. From the various simulation results obtained using the MATLAB/Simulink environment, it has been observed that the proposed FOPID‐DN‐based AVR system provided better performance as compared to different existing controllers. Abstract : This article presents a novel FOPID‐DN controller tuned using Equilibrium Optimizer algorithm for the AVR system. Various analyses have been performed to evaluate the efficacy of the FOPID‐DN controlled AVR system. Simulation results are compared with various existing PID, PIDA, and FOPID controllers to prove the superiority of the proposed approach. FOPID‐DN controller is also capable to handle nonlinearities and external disturbances in the AVR system. ​